2006
DOI: 10.1163/156855506776382691
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the chain-propagation mechanism of propylene polymerization catalyzed by traditional Ti-based Ziegler–Natta catalysts in view of recently developed catalysts

Abstract: The propagation mechanism of 1-alkenes, especially propylene, for newly developed catalysts such as metallocene catalysts and bis(phenoxy-amine)zirconium-based catalysts and traditional Ti-based Ziegler-Natta catalysts, and the relationship between the structure of the catalyst and the structure of polyolefins produced, was reviewed. We believe that the propagation mechanism of 1-alkenes, especially propylene, for traditional Ti-based heterogeneous catalysts and the relationship between the structure of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Stereospecific heterogeneous α-olefin polymerization has been a major research field since the first discovery of Ziegler-Natta (ZN) olefin polymerization catalysts. [1][2][3][4] Although most of the research efforts have been focused on the development of new catalytic systems for propylene polymerization, [5][6][7][8] the design and synthesis of efficient catalysts for the stereoselective polymerization of longer chain α-olefins have also attracted extensive research interests since the polymeric materials based on α-olefins could find variety of applications. Low molecular weight (MW) poly(α-olefin)s are used as base materials for lubricating oil formulation, while high MW ones are used as pour point depressant and drag-reducers.…”
Section: Introductionmentioning
confidence: 99%
“…Stereospecific heterogeneous α-olefin polymerization has been a major research field since the first discovery of Ziegler-Natta (ZN) olefin polymerization catalysts. [1][2][3][4] Although most of the research efforts have been focused on the development of new catalytic systems for propylene polymerization, [5][6][7][8] the design and synthesis of efficient catalysts for the stereoselective polymerization of longer chain α-olefins have also attracted extensive research interests since the polymeric materials based on α-olefins could find variety of applications. Low molecular weight (MW) poly(α-olefin)s are used as base materials for lubricating oil formulation, while high MW ones are used as pour point depressant and drag-reducers.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Industrial catalysts precursors containing magnesium compounds such as MgCl 2 or Mg(OEt) 2 in conjunction with TiCl 3 or TiCl 4 showed great performance in olefin polymerization; however, still there are lots of modifications of ZN catalysts varying in the way of preparation of the support [10][11][12][13][14] and differences in the active component compound structure and the presence of various modifying additives. [15][16][17][18] Lately, investigations have shown that doping a suitable amount of Lewis acids in MgCl 2 or Mg(OEt) 2 supports would be an effective way to improve their catalytic performance in α-olefin polymerization. The mostly used doping agents were based on different metal halides such as MnCl 2 , [2] ZnCl 2 , [3] NaCl, [4] AlCl 3 [5,6,19], and the mixture of metal halide with metalloids like ZnCl 2 -SiCl 4 system.…”
Section: Introductionmentioning
confidence: 99%
“…Although so much attention has been paid to the synthesis of polyolefins with a single‐site metal catalyst system, this mini‐review tries to direct a little attention to the ‘old’ and conventional Z‐N catalysts based on the fact that Z‐N catalysts are the most widely used and leading catalysts in industry due to their unique advantages such as low cost and high stereoregularity. Since the stereospecific polymerization of propylene with Z‐N catalysts has been widely reviewed and discussed, this mini‐review focuses solely on the highly stereospecific polymerization of butene‐1, isoprene and butadiene with supported Z‐N catalysts (Scheme ), and aims to present the supernatural catalytic features of supported Z‐N catalysts in α‐olefin and diene polymerizations especially in the last two decades.…”
Section: Introductionmentioning
confidence: 99%